INFLUENCES OF HEAT TREATMENT ON MECHANICAL BEHAVIOR AND MICROSTRUCTURE OF THE ExpLOSIVELy WELDED D GRADE STEEL / EN AW 5083 ALUMINIUM JOINT - Palaci, Y.; Olgun, M. (POLSKA AKAD NAUK, POLISH ACAD SCIENCES, INST METALL & MATER SCI PAS, 2021)
In this study, the effects of heat treatment on aluminum/steel structural transition joint (STJ) strength were analyzed with ram tensile tests to find the right welding conditions. Before ram tensile tests, the specimens were subjected to different heat treatments to simulate possible thermal conditions, which may occur during the welding of STJ to the steel side of ship construction. Temperatures were varied from 100 degrees C to 500 degrees C, and durations were changed between 5-25 minutes in the heat treatments. The results of the ram tensile tests indicated that tensile strength decreased above 300 degrees C. Micro-hardness test and microstructure examination were conducted to understand behavior change during ram tensile tests. The investigation showed that precipitation of the secondary hard phases with aging at interface above 300 degrees C, reduced the bonding between aluminum and steel materials, which lead to a decrease of strength, and also changed the mechanical behavior of the STJ during ram test from ductile to brittle fracture. If the temperature is below 500 degrees C and the duration is under 15 minutes, the STJ strength value meets the standard requirement. Short and rapid welding could be suggested to reduce heat buildup during welding.
Keywords: Triclad; Heat Treatment; Mechanical Properties; Dissimilar metal welding; INTERMETALLIC PHASES; BONDING ZONE; ALLOY; GROWTH; Metallurgy & Metallurgical Engineering